Authentication and Encryption in Cloud using Linear Algebra - Aruna, T (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing a new concept of Modern World and it combines all the service models and technologies together to deliver IT enterprise. The objective of this algorithm is to provide the security to end user to protect files or data from the unauthorized user. Privacy is an important issue for any technology through which unauthorized user can access your file or data in a cloud. I have presenting an encryption algorithm to deal with the privacy problems in cloud computing and protect the data stored in the cloud.